Stiffening Matrix Induces Age‐Mediated Microvascular Phenotype Through Increased Cell Contractility and Destabilization of Adherens Junctions. Issue 22 (3rd June 2022) - Schnellmann, Rahel; Ntekoumes, Dimitris; Choudhury, Mohammad Ikbal; Sun, Sean; Wei, Zhao; Gerecht, Sharon
Abstract: Aging is a major risk factor in microvascular dysfunction and disease development, but the underlying mechanism remains largely unknown. As a result, age‐mediated changes in the mechanical properties of tissue collagen have gained interest as drivers of endothelial cell (EC) dysfunction. 3D culture models that mimic age‐mediated changes in the microvasculature can facilitate mechanistic understanding. A fibrillar hydrogel capable of changing its stiffness after forming microvascular networks is established. This hydrogel model is used to form vascular networks from induced pluripotent stem cells under soft conditions that mimic young tissue mechanics. Then matrix stiffness is gradually increased, thus exposing the vascular networks to the aging‐mimicry process in vitro. It is found that upon dynamic matrix stiffening, EC contractility is increased, resulting in the activation of focal adhesion kinase and subsequent dissociation of β ‐catenin from VE‐Cadherin mediated adherens junctions, leading to the abruption of the vascular networks. Inhibiting cell contractility impedes the dissociation of β ‐catenin, thereby preventing the deconstruction of adherens junctions, thus partially rescuing the age‐mediated vascular phenotype. The findings provide the first direct evidence of matrix's dynamic mechano‐changes in compromising microvasculature with aging and highlight the importance of hydrogel systems to study tissue‐level changes with aging in basic and translational studies. Abstract : To mimic the aging matrix, a fibrillar hydrogel system capable of changing its stiffness after the formation of microvascular networks is presented. Upon dynamic matrix stiffening, endothelial cell contractility increases, resulting in dissociation of β ‐catenin from vascular endothelial‐cadherin mediated adherens junctions, thus destructing the vascular networks. This is the first direct evidence of aging matrix regulation of tissue microvascular network phenotype and possible therapeutic targets.